1994
DOI: 10.1007/bf00294356
|View full text |Cite
|
Sign up to set email alerts
|

Globoid cell leukodystrophy: comparison of neuropathology with magnetic resonance imaging

Abstract: Previous imaging studies in infants with globoid cell leukodystrophy (GLD) using computed tomography have demonstrated a reduction in cerebral white matter and increased density symmetrically in the regions of the thalami, periventricular white matter, and the internal capsules. Correlation of these findings with morphologic studies at necropsy has not been made. In particular, deposition of calcium has not been described. We have evaluated two children with GLD confirmed by the absence of leukocyte galactosyl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
14
0
1

Year Published

1997
1997
2017
2017

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(19 citation statements)
references
References 14 publications
4
14
0
1
Order By: Relevance
“…Studies performed in human beings and in canine models have shown that damage to myelin can be visualised by magnetic resonance imaging (MRI; Kuharik and others 1988, Percy and others 1994, Barkovich 2000, 2005, McGowan and others 2000). The appearance of myelin in MRI is based upon the water content in the myelin sheath, resulting in differences in T1‐ and T2‐relaxation times.…”
Section: Introductionmentioning
confidence: 99%
“…Studies performed in human beings and in canine models have shown that damage to myelin can be visualised by magnetic resonance imaging (MRI; Kuharik and others 1988, Percy and others 1994, Barkovich 2000, 2005, McGowan and others 2000). The appearance of myelin in MRI is based upon the water content in the myelin sheath, resulting in differences in T1‐ and T2‐relaxation times.…”
Section: Introductionmentioning
confidence: 99%
“…2,8,[12][13][14][15] In one of the individuals described by Feanny et al, 14 calcification was confirmed on autopsy. One of the cases reported by Percy et al 7 also demonstrated calcification in the deep white matter in areas undergoing degeneration and cyst formation. A further case has recently been described by Bonetti et al 16 Most recently, 17 extensive basal ganglia and white matter calcification has been reported in a child aged 6 months who had undergone a cord blood transplantation for Krabbe disease in the neonatal period.…”
Section: Discussionmentioning
confidence: 86%
“…The high attenuation areas are thought to correspond to areas of high concentration of globoid cells and proliferating glia. 4,7 MRI features are also characteristic and include periventricular and lobar white matter abnormalities, often with a radiating pattern of stripes, involvement of the posterior limb of the internal capsule and corpus callosum, and early involvement of cerebellar white matter, hilus of the dentate nucleus, and pyramidal tracts. CT and MRI provide complementary information.…”
Section: Discussionmentioning
confidence: 99%
“…A ressonância nuclear magnética de crânio mostra lesões de atrofia, principalmente em áreas onde a mielinização é mais precoce. Lesões simétricas na substân-cia branca com envolvimento do corpo caloso e atrofia cerebral progressiva também são descritas [12][13][14][15][16] .…”
Section: Discussionunclassified